Influence of Pd doping on morphology and LPG response of SnO2 - Vaishampayan, Mukta V.; Deshmukh, Rupali G.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2008)
In the present study nanocrystalline pristine and Pd-doped SnO2 (Pd:SnO2) with various mol% Pd have been synthesized by a modified Pechini citrate route. Transmission electron microscopy and X-ray powder diffraction studies were used to characterize the morphology, crystallinity, and structure of the SnO2 and Pd:SnO2. The response of the pristine SnO2 and Pd:SnO2 was studied towards different reducing gases. The 1.5 mol% Pd doping showed an enhanced response of 75 and 95% towards LPG at as low as 50 and 100 degrees C, respectively, which were quite large high value as compared with pristine SnO2 (38 and 35% at 50 and 100 degrees C, respectively). Structural characterization revealed that Pd doping reduced the crystallite size of SnO2 and helps in the formation of distinct spherical nanospheres at a calcinations temperature of 500 degrees C. Thus the increase in LPG response can be correlated with the spherical morphology, a decrease in the crystallite size (11 nm) due to doping with Pd as compared with the pristine SnO2 (26 nm) and main role of Pd as a catalyst. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: LPG sensor; nanospheres; palladium doping; tin oxide

Influence of process variables on growth of ZnO nanowires by cathodic electrodeposition on zinc substrate - Sheini, Farid Jamali; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A. (Thin Solid Films, 2009)
Influence of the deposition duration and electrolyte concentration on the structural and morphological features of the ZnO thin films, grown by cathodic electrodeposition on zinc substrate followed by annealing in air at 400 degrees C, have been investigated. The surface morphology of the as-synthesized films shows two distinct features, presence of `2-dimensional nanosheets' on the area near the electrolyte-air interface and `granular' nanostructures, below the interface region. However, upon annealing, the formation of ZnO nanowires, possessing length of several microns and diameter less than 20 nm, on the entire substrate is observed. The X-ray and selected area electron diffraction patterns clearly confirm the polycrystalline nature of the ZnO nanowires. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Annealing; Electrodeposition; Nanowires; photoluminescence; scanning electron microscopy; transmission electron microscopy; Zinc oxide

Investigations on Ru doped ZnO: strain calculations and gas sensing study - Navale, Shalaka C.; Ravi, V.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2009)
Pure and ruthenium (Ru) doped nano-crystalline zinc oxide (ZnO) powders were synthesized by using well-known citrate gel route. Citric acid acts as a chelating agent and thus helps in the formation of nanoparticles. The detailed X-ray diffraction (XRD) studies using Hall equation reveal that in the nanoscale dimensions, incorporation of Ru modulates the lattice strain. It is interesting to note that on Ru doping, the compressive strain present in the undoped ZnO changes into tensile strain. We have tested the response of these specimens individually for reducing gases like H(2), LPG (liquefied petroleum gas), C(2)H(5)OH (ethanol), CO, acetone and oxidizing gases like NO, and Cl(2). Undoped ZnO responses perceptibly to LPG while Ru doped sample highly senses ethanol vapors. This might be due to either change in composition on Ru doping or/and difference between basicity of LPG and C(2)H(5)OH vapors. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Ethanol sensor; LPG sensor; Nanomaterials; ruthenium

Influence of palladium on gas-sensing performance of magnesium ferrite nanoparticles - Darshane, Sonali L.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2010)
Commercial ferrites with high densities are mostly used in the electromagnetic devices, which require high temperature synthesis. In this article the gas-sensing characteristics of pure and Pd-doped MgFe(2)O(4) powder has been discussed. The synthesis has been carried out by using a simple molten salt method. This method facilitates rapid synthesis at comparatively lower temperature enabling formation of nanostructures, suitable for the gas-sensing application. Various physicochemical techniques have been used for the characterization of samples. X-ray diffraction analysis confirmed the single-phase formation of pure and Pd-doped MgFe(2)O(4) having crystallite size 15-20 nm. Pure MgFe(2)O(4) showed highest responses towards liquid petroleum gas (LPG) at 350 degrees C while, on doping with Pd the highest response shifted towards lower operating temperature of similar to 200 degrees C. Pure MgFe(2)O(4) exhibited some response towards 200 ppm of LPG which markedly increased on doping of palladium (Pd). The probable mechanism is proposed to explain the selective response towards LPG. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Doping; Ferrite; LPG sensor; Molten salt synthesis; Nanostructures

Influence of Pd-loading on gas sensing characteristics of SnO2 thick films - Bagal, L. K.; Patil, J. Y.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2012)
Nanocrystalline pristine and 0.5, 1.5 and 3.0 wt% Pd loaded SnO2 were synthesized by a facile co-precipitation route. These powders were screen-printed on alumina substrates to form thick films to investigate their gas sensing properties. The crystal structure and morphology of different samples were characterized by using X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques. The 3.0 wt% Pd:SnO2 showed response of 85% toward 100 ppm of LPG at operating temperature of 250 degrees C with fast response (8 s) and quick recovery time (24 s). The high response toward LPG on Pd loading can be attributed to lowering of crystallite size (9 nm) as well as the role of Pd particles in exhibiting spill-over mechanism on the SnO2 surface. Also selectivity of 3.0 wt% Pd:SnO2 toward LPG was confirmed by measuring its response to other reducing gases like acetone (CH3COCH3), ethanol (C2H5OH) and ammonia (NH3) at optimum operating temperature. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: LPG sensor; Palladium; SnO2; Thick film